Penerapan Metode Kisah pada Pembelajaran PAI di SDN 08 Surau Gadang Padang - Febriza, Zuhri; Wiza, Rahmi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The purpose of this study is to describe how the story method is applied by PAI teachers to the material I Am a Saleh Child in class IV SDN 08 Surau Gadang. The research method used in this research is qualitative with descriptive research type. Data collection techniques using observation, interviews, and documentation. The research subjects were teachers of Islamic Religious Education and fourth grade students at SDN 08 Surau Gadang. Based on the results of the study it can be concluded that by applying the story method to PAI learning in class IV it can increase the enthusiasm of students, they become easier to understand the subject matter and create a pleasant atmosphere in class and most students get satisfactory grades.